PENGARUH BELANJA BARANG DAN JASA, BELANJA MODAL DAN PERTUMBUHAN EKONOMI TERHADAP KAPASITAS FISKAL KABUPATEN DAN KOTA DI PROVINSI RIAU TAHUN 2011 - 2020 - Saparman Saparman; Syapsan Syapsan; Dahlan Tampubolon (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of spending on goods and services, capital expenditures and economic growth on fiscal capacity in districts/cities in Riau Province in 2011 – 2020. The data analysis method uses panel regression analysis with the EViews10 program. Panel data is a combination of time series and cross section data. The results of this study indicate that expenditure on goods and services has a negative and insignificant effect on fiscal capacity in districts/cities in Riau Province in 2011 – 2020. This means that changes in goods and services spending have not been able to affect changes in fiscal capacity in districts/cities in Riau Province. so this means contrary to the hypothesis. Capital expenditures have a significant positive effect on fiscal capacity in regencies/cities in Riau Province in 2011 – 2020. This means that an increase in capital expenditure can encourage an increase in fiscal capacity, this is because an increase in capital expenditure will encourage an increase in the provision of assets owned by the region so that the existence of assets This will be one of the sources of regional revenue, namely from levies and taxes so that it will encourage fiscal capacity and thereby increase fiscal capacity in districts/cities in Riau Province, this means that it is in line with the hypothesis. Economic growth has a significant positive effect on fiscal capacity in districts/cities in Riau Province in 2011 – 2020. This means that increased economic growth can encourage an increase in fiscal capacity, this is because an increase in economic growth will encourage an increase in income and the production of goods and services in the region. so that it will become one of the sources of regional revenue, namely from levies and taxes so that it will encourage fiscal capacity thereby increasing fiscal capacity in districts/cities in Riau Province, this means that it is in line with the hypothesis.